2013
DOI: 10.1259/dmfr.20120155
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic concordance between MRI and electrovibratography of the temporomandibular joint of subjects with disc displacement disorders

Abstract: Objectives: The aim of this study is to evaluate the diagnostic concordance of MRI and electrovibratography (EVG) of the temporomandibular joint (TMJ) in the diagnosis of articular disc displacement with reduction (ADDwR) and articular disc displacement without reduction (ADDw/oR). Methods: 50 patients (12 males, 38 females; mean age 37.46 6 15.64 years) with a hypothesis of disc displacement were selected. For each patient an MRI of the TMJ was performed. MRIs were evaluated sorting the 100 TMJs by kind of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…In a previous study, 16 it was possible to show a good agreement between the MRI diagnosis of disc displacement with reduction and the ESG peak morphology with a Cohen's kappa coefficient of 0.56. Furthermore, a specificity of 90.24% and a PPV of 90% of the ESG peak morphology with respect to the MRI diagnosis of disc displacement with reduction, indicate 1) rare false positive cases and 2) the presence of this morphology is related to a diagnosis of ADDwR in 90% of the observed cases.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous study, 16 it was possible to show a good agreement between the MRI diagnosis of disc displacement with reduction and the ESG peak morphology with a Cohen's kappa coefficient of 0.56. Furthermore, a specificity of 90.24% and a PPV of 90% of the ESG peak morphology with respect to the MRI diagnosis of disc displacement with reduction, indicate 1) rare false positive cases and 2) the presence of this morphology is related to a diagnosis of ADDwR in 90% of the observed cases.…”
Section: Discussionmentioning
confidence: 84%
“…Electrosonography (ESG) may be a useful method in the assessment of the disc position in suspected cases of internal derangement. 13,14 In a previous paper 16 the authors demonstrated that the presence of a peak-shaped track in ESG has high specificity for Articular Disc Displacement with Reduction (ADDwR) (90.27%). The use of ESG to support the clinical diagnosis of a disc displacement with 5 reduction was thus recommended when MRI is not available or when subjects cannot be analyzed by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is not so easy to detect the joint sounds clinically. 4 There are many objective and subjective methods have been developed to record and analyse the TMJ sounds ranging from simple palpation and auscultation to complex Electromyography (EMG), Jaw Tracking, Thermography, Sonography, Dopper Ultrasound, Magnetic Resonance Imaging (MRI), Arthrography, Arthroscopy, Computerized Tomography (CT) scan which are expensive and provide static information. In search of an inexpensive method which provides dynamic information about joint, a personal computer based tool -JVA was developed based on principles of motion and friction.…”
Section: Discussionmentioning
confidence: 99%
“…9 Deregibus, T Castroflorio et al showed 90 patiens with disc displacement, 90% specificity in disc displacement with reduction. 4 Ishigaki et al 7 reported a disc displacement with reduction generates a "click" in the lower frequencies (under 300 Hz) and a degenerative condition generates "crepitus" in the higher frequencies (over 300 Hz). 10…”
Section: Discussionmentioning
confidence: 99%
“…Many different systems, equipments and methods have been used in the past to accomplish the recording and analysis of TMJ vibration data. 5,10,13,18,20,21 More recent results from studies of electrovibratography, [23][24][25][26][27] joint vibration analysis (JVA), [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] sonography, [44][45][46] electro-sonography [47][48][49][50] and doppler auscultation [51][52][53][54] have been mixed, although far more successful classifications have been published than failures. However, a few dentists have been skeptical of the usefulness of TMJ vibration measurements.…”
Section: Introductionmentioning
confidence: 99%